Dangke: Pangan Lokal (Kajian Historis dan Nilai Budaya di Desa Pinang Kecamatan Cendana Kabupaten Enrekang) - Sri Fatmawati Mustamin; Mr. Jumadi; Dimas Ario Sumilih (Jurnal Kajian Sosial dan Budaya: Tebar Science, 2022)
This study aims to determine the history of local food made and known by the people in Pinang Village, Cendana District, Enrekang Regency, the traditional process of making dangke and its development, as well as the cultural value of dangke as local food. This research is a type of qualitative descriptive research. Data collection techniques were carried out using observation, interviews, and documentation. Based on the results of this study, it shows that: (1) The historical study of dangke is that the name "dangke" itself comes from Dutch when the Dutch officers patrolled the village of Curio, they were served dangke, as a guest of honor. The Dutch officers tasted the dish. After saying goodbye they said thank you for a very delicious meal, pronounced in Dutch â€œdank u wellâ€ as a thank you; (2) The traditional process of making dangke and developments to date is to take selected fresh dairy cow's milk, cook it on medium heat, add enough papaya latex and add a little salt, then stir until it forms lumps, after that the lumps are inserted into the coconut shell mold and pressed to form, after being removed from the mold then wrapped using selected banana leaves; and (3) Dangke is not only an ethnic identity of the people of Enrekang district but has cultural values â€‹â€‹of local wisdom in it, namely abstinence from redundant nature, open to knowledge and closed from bad influences and as a symbol of respect and appreciation.